Industria, comercio y arquitectura. Alemanes en la industrialización en Colombia (2016)
During the past three years, the University of Santo Tomas, Tunja, Colombia, TU Bergakademie Freiberg in Germany, and the Institute for New Industrial Culture (INIK) of Germany, have worked together on a research project that deals with the industrialization of Colombia, with the influence of German immigrants in this process. It is a strategy of bilateral cooperation that generates an important research benefit of the Germans’ presence in Colombia and their contributions to national development.In this process, it has been important to examine in particular how German influences have contributed to the development of Colombia’s industrial culture and its role for the future development of the country. The project has an interdisciplinary approach, integrating the disciplines of planning and design with history and cultural studies. In this context, there have been several trips with field research to both Colombia and Germany, in which students and teachers from both countries have taken part.This article shows part of the advancement of research, a result of both fieldwork and consultation from various sources, which is followed by a new phase of furthering the search for data about the characters and German companies mentioned here. German influence in the industry, mining, trade and architecture of Colombia is undeniable; the task now is to establish the permanence and significance of that legacy.